Factorial Structure of Cognitive Activity Using a Neuropsychological Test Battery - A. Ardila; M. Rosselli; J. R. Bateman (Behavioural Neurology)
A general neuropsychological test battery was assembled and individually given to a 98-subject sample, aged 11–12 years old. The battery included some basic and common tests routinely used in the evaluation of language, memory, spatial abilities, concept formation, and praxic abilities. Twenty-five different scores were calculated. A factor analysis with varimax rotation disclosed nine different factors, accounting for about 70% of the variance. Factor I was measured by a Sequential Verbal Memory test and Verbal Fluency subtests (“verbal factor”). Factor II was measured by the Wechsler Memory Scale Visual Memory subtests (immediate and delayed reproduction), and the Rey-Osterrieth Complex Figure (copy and immediate reproduction) (“non-verbal memory and constructional factor”). Factor III was measured by the WMS Logical Memory subtests (immediate and delayed; “verbal memory factor”). Factor IV was associated with fine movements (tapping subtests, right and left hand; “fine movements factor”). Factor V was specially measured by the Information subtest of the WMS and the Boston Naming Test (“verbal knowledge”). Factor VI represented a “praxic ability factor” (ideomotor praxis tests). Delayed Associative Learning subtest measured Factor VII; and Digits measured Factor VIII. Factor IX was a “mental control factor” (Mental Control subtest of the Wechsler Memory Scale). The implications of these results to theories relating to the structure of cognitive activity are discussed.